The Representation of the Palestine Occupation (1948) in the Poetry of the Palestinian Women Poets - Ezzat Molla Ebrahimi (زن در فرهنگ و هنر, 2010)
A group of Palestinians became refugees in neighboring Arab countries after their homeland was occupied by Israel. Other part of the population continued to reside in the occupied country at Karate Gerbil and Ghazi, but they have lost the peace, and the political stability and establishment. Consequently, this disordered situation affected Palestinian poetry.Refugee status, exile, massacre, pillage, confiscation of the land and the property, demolition and destruction, etc caused the Palestinian poets to reflect their compatriot's endless sufferings post 1948. This has strengthened the Palestinians’ adherence to their national poetry. Thus, the spirit of the resistance and the liberation of the occupied homeland have become the main goal of the Palestinian Mojahids to promote and support the National Palestinian Movement